MAHAR SERVICES (DOWRY NON MATERIAL) ACCORDING TO MAZHAB IMAM HANAFI AND MAZHAB IMAM SYAFI'I - Nur Hadi (Indonesian Journal of Islamic Law, 2018)
Abtrsak: The research aims to find out the opinion of Imam Abu Hanifah and the Imam of Shafi'i and the similarities in the differences in determining the Non-Material Mahar Law (services). This type of research is literature. The primary data sources are the books of the two priests, as well as the source of the secondary books of jurisprudence and books relating to research. Data was analyzed using descriptive, deductive, inductive, and comparative methods. The result: Disagreements between the two priests of the school were due to differences in law enforcement. Hanafi Imam in determining the status of the Mahar Non Material Law (services) uses the surah al-Nisa '24, al-Baihaqi hadith and he put forward qiyas, namely limiting the dowry to at least ten dirhams, and dowry in the form of Qur'anic teaching to candidates unauthorized wife. Reserve Imam Shafi'i using the surah al-Nisa '24 and al-Bukhari's hadith, which does not limit the lowest dowry, such as sewing clothes or teaching the Koran to his wife and any benefits that are owned and lawful in price and having the value of simplicity at the dowry is preferred, he looked at the sunnah, that it is not excessive if it is legitimately used as a dowry, looking at zhahir verses and hadith.